A Study of Millisecond Blasting on High Bench at Barun Iron Ore Operation. (3rd December 2021) - Zhang, Pengfei; Bai, Runcai; Sun, Xue; Li, Haoran; Fei, Honglu; Bao, Shijie
Abstract : To improve the productivity and efficient of modern large-scale open-cut mines, a number of technologies are developed and trialed, including new blasting equipment, larger blasting holes, high benches, air spacing, and short-delay blasting within holes. However, the relative blasting parameters need field calibration and further investigation of theories on these techniques are required. This paper studied the open-cut bench blasting at Barun Eboxi Mine of Baotou Iron and Steel Group via theoretical analysis on shock wave, numerical simulation, and field test. According to the technical conditions of the site, three sets of vertical boreholes at 310 mm diameter were drilled on 24 m high batter; and three sets of air-spaced charges were set up. The digital electronic detonator was used to initiate at millisecond intervals. The study found that under the condition of 24 m high bench, the use of intermediate air interval is beneficial to the rock fragmentation. The delay time within the hole is 3-8 ms. The bottom of the lower explosives and the top of the upper explosives were devised for initiation to optimize the initiation location. The peak effective stress points are 63.6%, 52.2%, and 8.9% higher, respectively. The field test of high-bench intrahole millisecond blasting in Barun Eboxi mine shows that the intrahole millisecond blasting parameters proposed in this study are feasible.